Conflict and Culture: Ways of Effective Management - Boris Vasilievich Kabylinskii (Управленческое консультирование)
Development of the theory and methodology of conflict management and implementation of technologies of solving contradictories have to be taken out with considering formation of cultural identity. In the administrative theory influence of cultural factors on dynamics of conflict processes is not fully studied is seldom revised during realization of practical measures in conflict management. Factors of culture genesiswhile defining the course of confrontation of conflict parties, cross-cultural channels of communication, classification of mechanisms of decision-making in the theory and practice of management of the conflicts are given in the article.